2020
DOI: 10.1002/cbin.11458
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes are associated with tissue remodeling and angiogenesis during the postlactational involution of the mammary gland in gerbils

Abstract: The postlactational involution of the mammary gland is a complex process. It involves the collapse of the alveoli and the remodeling of the extracellular matrix, which in turn implies a complex set of interrelations between the epithelial, stromal, and extracellular matrix elements. The telocytes, a new type of CD34‐positive stromal cell that differs from fibroblasts in morphological terms and gene expression, were detected in the stroma of several tissues, including the mammary gland; however, their function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…We found that vascular telocytes in the prostate produce VEGF, which indicates the participation of these cells in angiogenesis. This contribution by the telocytes was also verified in the lung 3 and in the mammary glands 50 . With regard to the establishment of a pro-inflammatory microenvironment, our data indicate that telocytes do not actively secrete pro-inflammatory cytokines, such as TNFα and IL-6, in the prostate.…”
Section: Discussionsupporting
confidence: 54%
“…We found that vascular telocytes in the prostate produce VEGF, which indicates the participation of these cells in angiogenesis. This contribution by the telocytes was also verified in the lung 3 and in the mammary glands 50 . With regard to the establishment of a pro-inflammatory microenvironment, our data indicate that telocytes do not actively secrete pro-inflammatory cytokines, such as TNFα and IL-6, in the prostate.…”
Section: Discussionsupporting
confidence: 54%
“…In a 2020 original paper, Sanches et al examined the mammary gland of the Mongolian gerbil with a goal to perform an ultrastructural and immunohistochemical study of TCs during lactation and post-lactational involution. The authors observed that their function was closely associated with matrix metalloproteinase 9 (MMP-9) and vascular endothelial growth factor (VEGF), suggesting their capacity for ECM remodeling and angiogenesis regulation, respectively [46].…”
Section: Morphological and Functional Specifics Of Frs Telocytesmentioning
confidence: 99%
“…The involution of post-lactational mammary gland is featured as alveoli collapse and ECM remodeling. TCs involved actively in such involution process in Mongolian gerbil, by surrounding collapsed alveoli and breast ducts with synthesis of Matrix Metallopeptidase 9 (MMP9) and VEGF, which was essential for ECM digestion and remodeling, and angiogenesis respectively 13 . Therefore, TCs have therapeutic potential in maintaining the dynamic balance of CAFs or ECM either in carcinoma of breast or fibrotic diseases.…”
Section: Protection Against Fibrosismentioning
confidence: 99%
“…1 ). In addition, TCs can establish contacts with the connective extracellular matrix (ECM) 12 14 . With the aid of focused ion beam–scanning electron microscope (FIB-SEM) tomography, Tps present narrow and flattened (ribbon-like) structures and form 3D network by adherent homocellular junctions between TCs in heart and skin tissues; thus, strengthening the understanding of TCs’ spatial morphology 5 , 15 .…”
Section: Introductionmentioning
confidence: 99%